Administration of Glucosylceramide Ameliorated the Memory Impairment in Aged Mice. (3rd April 2013) - Lee, Yeonju; Oliynyk, Sergiy; Jung, Jae-Chul; Han, Jeong Jun; Oh, Seikwan
Abstract : The function and the role of glucosylceramide have not been well studied in the central nervous system. This study was aimed to investigate the possible roles of glucosylceramide in memory function in aged mice. Glucosylceramide (50 mg/kg, p.o.) showed memory enhancing activity after 3-month treatment in the aged mice (C56BL/6, 18–20 months old) through Y-maze, novel objective test, and Morris water maze test. Long-term treatment of glucosylceramide decreased the expression of iNOS and COX-2 in the brain of aged mice. The LPS-induced mRNA level of iNOS, COX-2, IL-1 β, and TNF- α was reduced by the acute treatment with glucosylceramide in adult mice. These results suggest that glucosylceramide plays an important role in anti-inflammatory and memory enhancement, and it could be a potential new therapeutic agent for the treatment of neurodegenerative diseases such as Alzheimer's disease.